Devouring images: Hélio Oiticica's anthropophagic quasi-cinema. (11th March 2019) - Butler, Alison
Abstract: Between 1970 and 1978, while living in New York City, the Brazilian artist Hélio Oiticica, working with filmmaker Neville d'Almeida, conceived a series of projected image installations entitled Cosmococas . This essay considers these works in relation to their historical moment, as an alternative conception of expanded cinema, influenced by North American practices but inflected by Oiticica's own cultural formation and his engagement with the Tropicália movement. Key to this alternative conception is Oiticia's use of separate media elements which interrelate via the body of the spectator, and his use of still images, to which, like his parangolés (capes, banners and tents made from layers of painted fabric and other materials) the spectator-performer brings movement. In contrast to the North American conception of expanded cinema as immersive multimedia, Oiticica theorized his work as 'quasi-cinema', a fragmentary form that explodes film into 'moment-frames', negating 'the unilateral character of cinema spectacle' in order to create a space for active participation of a kind not normally associated with cinema. Across a variety of his writings, including theoretical texts and personal correspondence, Oiticica repeatedly describes media as 'devouring'. Writing about the television set included in his Tropicália installation, he describes a 'terrible feeling […] of being devoured by the work'. The inclusion in the Cosmococas of images of cultural icons who died at the height of their fame – Jimi Hendrix and Marilyn Monroe – resonates with this notion of mass media devoration. The intermedial strategies deployed by Oiticica in his quasi-cinema projects are essentially anthropophagic, absorbing North American media images and forms as a way of preventing the culture of his host nation from devouring him.